ESTIMATE OF CHERNOZEM ERODIBILITY LEVEL ACCORDING TO THE HUMIFICATION DEGREE - B. M. Kogut (Бюллетень Почвенного института им. В.В. Докучаева, 2015)
A short review of literature sources is presented to characterize the eroded soils according to their humus content. Traditional diagnostic indicators of the soil erodibility level based upon the humus status are the following: (1) decrease in the thickness of humus horizons in eroded soils in percentage of that in uneroded soil (standard); (2) decline in the humus storage in the eroded soil profile in percentage of that in uneroded soil (standard). It is worth emphasizing that the choice of the uneroded soil standard is a rather labor-consuming study in field and assumes an expert (subjective) character that is highly dependent on the soil scientist’s skill. It is shown that the main shortcomings of the available gradation for eroded soils consist in the absence of approaches to give their objective estimate and recommendations for permissible levels of soil erodibility taking into complete account the humus content in these soils. In the Russian Federation there is a gradation of arable soils (including chernozems) according to the humus content in the plough horizon. It contains four classes (less than the humus minimum, low, moderate and high humus content). In this paper it is recommended to give the gradation of eroded soils with the minimal humus content. The level of chernozem erodibility should be estimated as based upon the minimal and critical humus content. The minimal humus content is interpreted by Kërshens, whereas the critical humus content - by Kiryushin and Ganzhara. A gradation scale of soil erodibility is presented to estimate its permissible, non-permissible and critical levels. It is exemplified by the gradation of chernozem soils in Russia and Germany.